Availability and type depository of twelve Japanese plant bug species (Hemiptera: Heteroptera: Miridae) - Yasunaga, Tomohide; Schwartz, Michael D.; Aukema, Berend (Zootaxa, 2012)
For twelve nominal species of Miridae described from Japan by Yasunaga and his colleagues (Yasunaga, 2005; Yasunaga & Miyamoto, 2006; Yasunaga & Schwartz, 2005), no information is given on the type depositories of the holotypes, making these names unavailable according to Article 16.4.2 of the International Commission on Zoological nomenclature (ICZN 1999). We describe them here as new species and make their names available with the original authorship from the date of publication of this correspondence. For each new species, a reference is given to the published description, satisfying the conditions of Article 13.1.2 (ICZN, 1999).